Education and Skill Mismatches in Maptaphut Industrial Estate, Thailand - Varakamin, Duangjan (Journal of Reviews on Global Economics, 2017)
This paper examines educational and skill mismatches by using primary data from Maptaphut Industrial Estate, Rayong Province, Thailand, conducted from 226 respondents. Ordinary least squares (OLS) and unconditional quantile (UQR) regressions are used to examine the mismatches on earnings. The empirical findings are as follows: (1) returns to education of high income workers are larger than average income workers; (2) education mismatches affect earnings, such that over-education is statistically significant, whereas under-education is not significant, for both the OLS and UQR estimates; (3) UQR provides more information on size of the over-education to the returns on schooling; (4) specific training for some job positions also indicates educational and skill mismatches; and (5) firms should invest in training for workers to reduce weaknesses in educational mismatches.